“UNA ACCIÓN CONTRA EL SILENCIO”. NUEVAS FORMAS DE DENUNCIA DE DELITOS DE LESA HUMANIDAD EN URUGUAY. UNA REFLEXIÓN A PARTIR DE OCTUBRE DE 2011. - ALONSO, JIMENA (Universidad Nacional del Litoral, 2015)
The thirty years that passed since the end of the civil-military dictatorship (1973-1985) in Uruguay, were marked by obstacles to the prosecution of crimes committed during state terrorism. In October 2011, at the request of a group of citizens from different social context, 180 complaints were presented at several police stations in Montevideo involving cases of human rights violation. United under two slogans : “I take responsibility” and “Present charges for all” the actions defied hegemonic forms of protest construction and production of speeches on historical memory. We analyze the persistence of ambivalence between speeches and actions carried out under the banner of truth, justice and reparation, from a concrete case study, which allowed the production of new forms, sensitivities and counter senses.